Teacher Strategies Assisted by Game-Based Learning (GBL) Models in Overcoming Students' Low Learning Motivation at Wali Songo Madrasah Tsanawiyah - Wahyu Alifia; Andryadi; Dedi Yuisman (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the low learning motivation of students at MTs Wali Songo, as reflected in their limited participation, lack of attention during lessons, and low engagement in classroom activities. The study aimed to describe the condition of students' learning motivation, teachers' strategies assisted by the Game Based Learning (GBL) model to overcome low learning motivation, students' responses to the implementation of GBL, the supporting and inhibiting factors, and the impact of GBL on students' learning motivation. This research employed a qualitative approach. Data were collected through observations, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that students' low learning motivation was influenced by both internal and external factors. Teachers implemented Game Based Learning systematically through planning, implementation, and evaluation stages, creating a more interactive, enjoyable, and student-centered learning environment. Students responded positively to the implementation of GBL. Its successful implementation was supported by teachers' creativity, the principal's support, students' enthusiasm, and adequate learning facilities, although limited instructional time and differences in students' academic abilities remained challenges. Overall, the implementation of Game Based Learning effectively enhanced students' learning motivation, active participation, self-confidence, collaboration, and engagement in the learning process.